The Time Series Dynamics of Foreign Direct Investment and Economic Development - Zhang, Yi (Advances in Social Sciences Research Journal, 2017)
The relationship between FDI inflows and economic growth has received immense attention among policy makers and business leaders but no consensus has been reached. By using Engle-Granger (1987) bivariate cointegration procedure, this paper analyzes the impact from FDI inflows to GDP as well as the causality between these two with the time series data from 1966 to 2005 for 5 countries. The results reveal that the growth effect of FDI inflows is still ambiguous for the 5 countries, while all of these countries have a significant effect from GDP on FDI inflows.